American manifesto : saving democracy from villains, vandals, and ourselves - Garfield, Bob (Counterpoint, 2020)
"Why is our society in the fix it is in? Is it all Trump's fault? Well, no. As often observed, Trump is a symptom of a virus has been incubating for at least 50 years and maybe 150. But not often observed is where the virus is imbedded: in the psychic core of identity. This book explores the primacy of identity in American society and makes the argument that hyper-polarization was not only predictable but inevitable, based on such unlikely causal bedfellows as biology, multiculturalism and collateral damage from the American Dream"--